2022
DOI: 10.1371/journal.pone.0266897
|View full text |Cite
|
Sign up to set email alerts
|

Impact of medication on blood transcriptome reveals off-target regulations of beta-blockers

Abstract: Background For many drugs, mechanisms of action with regard to desired effects and/or unwanted side effects are only incompletely understood. To investigate possible pleiotropic effects and respective molecular mechanisms, we describe here a catalogue of commonly used drugs and their impact on the blood transcriptome. Methods and results From a population-based cohort in Germany (LIFE-Adult), we collected genome-wide gene-expression data in whole blood using in Illumina HT12v4 micro-arrays (n = 3,378; 19,974… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Furthermore, using Mendelian randomization, the authors identified a bidirectional causal relationship between BP and arterial stiffness. 8 However, Rode et al 14 showed that PWV shared a common genetic architecture with BP although the Mendelian randomization analyses conducted on this cohort suggested that arterial stiffness was a consequence rather than a cause of increased BP. As only 2 studies are available, with some conflicting results, additional data using Mendelian randomization may be needed to better ascertain the existence and direction of causality linking BP and arterial stiffness.…”
Section: Correlations Between Bp and Pwvmentioning
confidence: 83%
See 2 more Smart Citations
“…Furthermore, using Mendelian randomization, the authors identified a bidirectional causal relationship between BP and arterial stiffness. 8 However, Rode et al 14 showed that PWV shared a common genetic architecture with BP although the Mendelian randomization analyses conducted on this cohort suggested that arterial stiffness was a consequence rather than a cause of increased BP. As only 2 studies are available, with some conflicting results, additional data using Mendelian randomization may be needed to better ascertain the existence and direction of causality linking BP and arterial stiffness.…”
Section: Correlations Between Bp and Pwvmentioning
confidence: 83%
“…In our study, PWV and SBP showed higher phenotypic correlation, albeit with few genetic codeterminants, whereas PWV and DBP showed more moderate phenotypic correlation (although remained <0.30) but with higher genetic codeterminants. There is evidence of a positive correlation between hypertension and arterial stiffness, 14,25 although the potential genetic link between BP and PWV has been sparsely investigated until recently. Cecelja et al 8 identified >50% of shared genes between BP and PWV when assessing bivariate heritability, although accounted for only a small proportion of the total phenotypic correlation.…”
Section: Correlations Between Bp and Pwvmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, combined training reduced estimated PWV in SHR, which was a very positive response, since arterial stiffness is considered an important marker of vessel health, an indicative of subclinical organ damage and predictor for the future cardiovascular events (Scuteri et al, 2020;Shchetynska-Marinova et al, 2021). Clinical measurement of PWV has been suggested to early control the development of arterial stiffness, in both patients with increased cardiovascular risk and the general population (Jannasz et al, 2019), since arterial stiffness may be independent of the BP values (Celik et al, 2017;Guers et al, 2019;Rode et al, 2020). There are some metaanalyzes comparing the effects of different types of exercise (aerobic, resistance, combined and high intensity interval training) on PWV, however they include hypertensive and normotensive individuals (Martinez-Vizcaino et al, 2019), which challenge the interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Third, there is significant variability of transcriptome profiles depending on nutrition 37 , infection 38 , medication 39 , sex 40,41 , and age 42 . This variability may limit current global RNA data analysis in the diagnostic context.…”
Section: Boxmentioning
confidence: 99%